Letters to Gorbachev : life in Russia through the postbag of Argumenty i Fakty - McKay, Ron (Michael Joseph, 1991)
"Letters to Gorbachev is the voice of the people of Russia as they question every aspect of life from the position of the Soviet Jews to the unavailability of sugar."--Back cover.